Multidimensional Poverty, Social Networks: Spatial Neighbourhoods on Poverty Eradication in Tumpang District, Malang Regency - Ismu Rini Dwi Ari; Budi Soegiarto Waloejo; Septiana Hariyani (Diponegoro University, 2021)
Poverty is multidimensional problem of the development that cause human difficulties in accessing public facility and infrastructure. Along with target of SDGs regarding poverty alleviation, main aims of this research are i) measure poverty level through three dimensions – health, education and standard of living of the Multidimensional Poverty Index (MPI), and ii) scrutinize influential variables of the poverty through Spatial Regression Analysis whereby physical as well as social variables are put it together in the model. This research would like to propose a set of research approach on how dealing with poverty in a certain area. Area of study is Tumpang district in Malang Regency, East Java Province consist of 15 villages, wherein at about 36,61% family are receiver of the Raskin (Beras Miskin – Poor Rice) program as one of the poverty alleviation programs in Indonesia. Both field observation as well as depth interview are conducted towards 274 head of households. Result study finds out that there are five villages which have high value of MPI in Tumpang District, namely Duwet Krajan, Duwet, Benjor, Tulusbesar and Kidal, and the two dimensions – education and living standard give significant contribution to the poverty. Next, poverty in the research area has influenced by both social relations among residents within a village as well as geographical location of the nearest neighbourhoods. Then, eradication poverty is necessary to put consideration on strengthening ‘constructive’ social relations among residents through their existence community groups.